Cone Beam Computed Tomographic Evaluation and Diagnosis of Mandibular First Molar with 6 Canals - Shiraz Pasha; Bathula Vimala Chaitanya; Kusum Valli Somisetty (Case Reports in Dentistry)
Root canal treatment of tooth with aberrant root canal morphology is very challenging. So thorough knowledge of both the external and internal anatomy of teeth is an important aspect of root canal treatment. With the advancement in technology it is imperative to use modern diagnostic tools such as magnification devices, CBCT, microscopes, and RVG to confirm the presence of these aberrant configurations. However, in everyday endodontic practice, clinicians have to treat teeth with atypical configurations for root canal treatment to be successful. This case report presents the management of a mandibular first molar with six root canals, four in mesial and two in distal root, and also emphasizes the use and importance of Cone Beam Computed Tomography (CBCT) as a diagnostic tool in endodontics.